Pulse Oximetry: The Fifth Vital Sign of Neonates - Das, JC (Journal of Bangladesh College of Physicians and Surgeons, 2012)
When supplementation of oxygen is inappropriate there is chance of development of either hypoxia or hyperoxia. During oxygen therapy, oxygen level should be maintained within a target-able range through proper monitoring. Pulse oximetry is a useful convenient and reliable monitoring system. The principle of working of pulse oximeter is based on the fact that oxyhaemoglobin and deoxyhaemoglobin absorb light at the red end of the spectrum differently; Deoxyhaemoglobin absorbs more red than infrared and oxyhaemoglobin more infrared than red. The ‘emitter’ of the probe of pulse oximeter sends equal intensities of red and infrared light into the tissue. The ‘sensor’ detects the ratio of red to infrared that emerges. From this information the proportion of oxyhaemoglobin to deoxyhaemoglobinthat is, the percentage saturation of hemoglobin with oxygen is calculated and displayed to the monitor of the instrument. The main advantage of pulse oximeter is that it is noninvasive, less complex, does not require calibration, provides continuous measurement of hemoglobin-oxygen saturation (SpO2), fast response time and high accuracy. Limitations of accuracy of pulse oximetry lie on poor perfusion, hypoxic events, hyperemia, severe anemia, dyshemoglobinemias, high oxygen partial pressures (PaO2), superficial pigments, black skin of infant, motion artifact, pressure on sensor, presence of abnormal dye, light and electrical interference. It is essential to remember the limitations of this instrument before going to pulse oximetry. Key words: Pulse oximeter; neonate; vital signs; principals of working; limitations.